دور مؤشرات قائمة التدفقات النقدية في تقييم قدرة المؤسسة على التزاماتها دراسة حالة المؤسسة الوطني للهن سوق اهراس - سيف الدين كافي; محمد دحامنية (My University, 2021)
This study are intended to underline the role of indicators in statement cash flows including capacity assessment of the enterprise to satisfy the needs of the national enterprise Souk Ahras and to ensuring the objectives of the study we have adopted data from documents about the enterprise(budget chart of results accounts statement of cash flows ) during the period (2012-2015) The theoretical aspects visibility detail of cash flows including capacity assessment of the enterprise the applied of aspects we did a practical study on the national fat enterprise Souk Ahras and our findings are the important role of statement cash flows on capacities assessment Of the enterprise to satisfy the obligations through the solvency ration and budget policy. and we got that contribution of operational activities establishment the safe while investment activities and financing consuming the treasury stock resulting in achieving negative net treasury. We came up that the national fat enterprise does not have enough liquid to coven all obligations in the short term. ................................................................ هدفت هذه الدراسة إلى إبراز دور مؤشرات قائمة التدفقات النقدية في تقييم قدرة المؤسسة على سداد إلتزماتها للمؤسسة الوطنية للدهن ولاية سوق أهراس ولتحقيق أهداف هذه الدراسة قمنا بالإعتماد على البيانات المستخرجة من الوثائق المحاسبية _ المتوفرة لدينا عن المؤسسة الميزانية، جدول حسابات النتائج و قائمة التدفقات النقدية خلال الفترة 2015 2012 قمنا في الجانب النظري بتسليط الضوء بشكل مفصل على قائمة التدفقات النقدية وتقييم قدرة المؤسسة على سداد الإلتزمات المالية اما في الجانب التطبيقي فقد قمنا بدراسة تطبيقية حول المؤسسة الوطنية للدهن سوق اهراس وقد توصلنا إلى مجموعة من النتائج من أهمها أن لمؤشرات قائمة التدفقات النقدية دور في تقييم قدرة المؤسسة على سداد التزماتها وذلك من خلال تقييم جودة سيولتها وربحيتها وسياستها التمويلية كما توصلنا أيضا ان الأنشطة التشغيلية تساهم في تشكيل الخزينة بينما الأنشطة الإستثمارية والتمويلية تستهلك الخزينة وهذا ما ادى إلى تحقيق خزينة صافية سالبة كما توصلنا إلى أن المؤسسة الوطنية للدهن لاتملك سيولة كافية لتغطية كل التزماتها على المدى القصير.